Rapid synthesis of magnetic microspheres poly(glycidyl methacrylate-co-styrene) by photopolymerization - Sharina Abu Hanifah,; Normah Hamzah,; Lee, Yook Heng (Universiti Kebangsaan Malaysia, 2013)
Three compositions of glycidyl methacrylate and styrene were added with Fe3O4, ethylene glycol dimethacrylate (EGDMA), poly vinyl alcohol (PVA) and 2, 2-dimethoxy-2-phenylacetophenone (DMPP). Fe3O4 were dispersed within monomers and were exposed to the ultraviolet radiation for polymerization process. The Fe3O4 particles were introduced to enhance physical and chemical properties of the polymers. The thermal properties of polymer were improved after addition of styrene and Fe3O4. Vibrating sample magnetometer (VSM) also exhibits copolymer with soft ferromagnetic properties. Field emission scanning electron microscopy (FESEM) showed the size of magnetic polymer microspheres were from 0.5 to 1.5 μm. The rough surface was also observed due to the presence of styrene.